Impact of an educational action on breastfeeding and family planning on maternity women in a public maternity (Research, Society and Development, 2023)
Family planning in the immediate postpartum period is a proven practice that has a great impact on reducing unwanted pregnancies. The objective was to analyze the effectiveness of an educational intervention on family planning and the benefits of breastfeeding. This is a prospective, case-control study, carried out in a public hospital in Timon-Maranhão. 132 postpartum women were included in the immediate postpartum period, randomly distributed in: Control and Intervention Group. It was found that the use of contraceptives and breastfeeding were higher in the intervention group (78.8% and 68.2%, respectively). The use of formula was higher in the control group (36.4%). The most used contraceptive method in the groups was the oral contraceptive (38.5% and 33.3%, respectively). It was found that educational activities for puerperal women are effective, as a higher prevalence of breastfeeding and use of contraceptive methods was observed in the intervention group. The educational actions contributed to the formation of behaviors and adoption of attitudes that allow a better quality of life for mother and baby.